From the Editor - Disthabanchong, Sinee (Journal of the Nephrology Society of Thailand, 2024)
Time flies—it has already been two years since I took the role of editor-in-chief of JNST. Over this period, the journal has been very well received, with a rapid increase in views and downloads. We have maintained a rigorous double-blind peer review process for all submitted articles. I am also pleased to share that Q1-ranked journals have cited at least two articles published in JNST in 2023. In terms of efforts to support the inclusion of JNST in international databases, the editorial team has submitted various documents for quality evaluation by the Thailand Citation Index, with results expected by January 2025. Additionally, the editorial team has planned to request Digital Object Identifier (DOI) numbers for all articles published in the journal from 2025 onward, aiming to enhance article accessibility. In this final issue of 2024, we have included a section on the Endowed Lectureships that were presented throughout the year. The Professor Emeritus Sa-nga Nilvarangkun, MD, Endowed Lectureship was delivered by Professor Thanom Supaporn, who spoke on the topic “National Policy & Sustainability of the Thailand Dialysis Program.” The Professor Emeritus Visith Sitprija, MD, Ph.D., Endowed Lectureship was presented by Professor Chairat Shayakul, who discussed “From Cloning to Clinic.” Short biographies of both distinguished lecturers and summaries of their presentations can be found in the Endowed Lectureship section of the journal. Finally, I hope that JNST remains a sustainable resource for academic articles on kidney diseases. It serves as an excellent platform for both local and international researchers to submit their work, facilitating the dissemination of new knowledge that can be recognized and accessed globally. As we welcome the New Year of 2025, I wish everyone dedicated to the care of kidney disease patients much happiness and prosperity.